ANATOMICAL STUDY OF THE ANNULAR CIRCUMFERENCE OF ATRIOVENTRICULAR VALVE WITH ITS CLINICAL CORRELATION. - Dr. Pavan Kumar Mahato; Shailendra Singh (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Introduction: - The human heart comprises four chambers with openings to facilitate blood inflowand outflow. These openings are safeguarded by valves that ensure planned and controlled bloodflow. The annulus, the periphery where the valves are attached, plays a crucial role in this process.Two atrioventricular valves, tricuspid and mitral (bicuspid), are named after the number of cusps theypossess and are located between the atria and chambers on both sides. The pulmonary valve regulatesblood flow in the pulmonary trunk while the aortic valve regulates the flow through the aorta.Materials and Methods: - The study took place in the anatomy department of Index MedicalCollege Indore, Madhya Pradesh , where 45 formalin-fixed heart specimens were examined. Thehearts were dissected, allowing for visual examination of the interior to identify the tricuspid andbicuspid valves. Results:- Our current study observed that the annular Circumference of theTricuspid valve ranges from 46.09 to 131.92 mm, with a mean of 90.28±17.86. While annularCircumference of the bicuspid Valve ranges from 64.18-128.15 mm with a mean of 84.11 ±14.25Conclusion:- A thorough understanding of the anatomical features of the atrioventricular valve canenhance our comprehension of its structure and function. This knowledge can play a key role inimproving the outcomes of conservative treatments and facilitating a return to normal anatomical andfunctional states